INFLUENCE OF ESSENTIAL OILS ON IMPROVING SLEEP: A SCIENTIFIC REVIEW - Silva , Thainara Pereira da (2024)
Sleep quality plays a fundamental role in promoting health and well-being. In this article, we will explore the fascinating influence of essential oils on improving sleep. As we look to address the relaxing and therapeutic properties of these oils, we will examine how their application can be an effective strategy for optimizing sleep quality and providing benefits for the body and mind. Objectives: Given the above, the objective of the study is to analyze the improvement of sleep through essential oils. Methodology: The research was carried out through online access in the Scientific Electronic Library Online (SCIELO), PubMed, Latin American Caribbean Literature in Health Sciences (LILACS). in the month of January 2024. Analytical interpretation of articles was carried out on the theme Aromatherapy and essential oils and their relationship to sleep quality. Upon reading, the articles were subjected to inclusion and exclusion criteria, within the inclusion criteria articles were considered originals, which addressed the topic and allowed full access to the study content, published between 2015 and 2023, in Portuguese and English. The exclusion criterion was imposed on those works that were not in these languages, and that were not related to the objective of the study. Thus, there were a total of 31 scientific articles for the narrative literature review. Results and Discussions: Certain essential oils, such as lavender and chamomile, have shown significant potential in reducing insomnia and promoting deeper sleep. The interaction of these compounds with receptors in the central nervous system appears to play a crucial role in these beneficial effects. It is crucial to consider the mechanisms underlying these effects. Aromatherapy, by inhaling essential oils, can influence the limbic system, regulating brain activity associated with emotions and sleep. Additionally, the release of certain compounds during inhalation can impact neurotransmitters, such as serotonin, which play a role in regulating sleep. Conclusion: In short, essential oils, notably lavender, demonstrate promising potential in improving sleep quality. While the results are encouraging, it is essential to continue research to consistently validate these effects and fully understand the underlying mechanisms. Individuality in response to essential oils highlights the importance of personalized approaches. Therefore, considering the positive impact observed, the careful inclusion of these natural resources can offer a valuable complementary option for those looking to improve their sleep naturally.